EFEK MODERASI KOMPENSASI PADA PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA, DAN MOTIVASI KERJA, TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI UD. BAROKAH KERUPUK DO’A IBU KABUPATEN SITUBONDO - Sya’diya, Yuli Halimatus; Minullah, Minullah; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Human resource management is the science and art of managing the workforce effectively and efficiently, with a focus on placing the right people, in the right positions, and at the right time. The success of an organization depends heavily on its ability to align the needs of the company, with the potential of HR that meets applicable standards and procedures to achieve company goals. The purpose of this study is to analyze and test the effect of Work Discipline, Work Environment, and Work Motivation on Work Productivity with Compensation as a moderating variable at UD. Barokah Kerupuk Do’a Ibu, Situbondo Regency. This research is an explanatory research. The populations to be tested in this study were employees of UD. Barokah Kerupuk Do’Ibu, Situbondo Regency. The sampling technique was determined by saturated sampling. The data analysis and hypothesis testing in the study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Work discipline has a negative but insignificant effect on Work productivity, Work environment has a negative and significant effect on Work productivity, Work motivation has a positive but insignificant effect on Work productivity, Compensation is insignificantly able to weaken the role of Work discipline in reducing Work productivity, Compensation is significantly able to strengthen the role of the Work environment in increasing Work productivity, Compensation is significantly able to strengthen the role of Work motivation in increasing Work productivity.